The Effects of Cognitive Flexibility on Teacher’s Readiness To Implement the Merdeka Curriculum - Idawati, Idawati; Akrom, Abdul Hayyi; Asy’ari, M. Hasanil (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This article aims to determine cognitive flexibility in influencing teacher readiness for implementing the "imerdeka curriculum" in schools. Research method used a regression test using comprehension survey data using a questionnaire to see differences in the level of teacher readiness in implementing the "merdekat curriculum" based on high and low levels of teacher cognitive flexibility. The research subjects were 30 teachers of MI (Islamic Elementary School) in NW Dasan Lekong, Sukamulia Regency, and MI Hamzanwadi Toya, Aikmel Regency, two private schools in East Lombok, West Nusa Tenggara, Indonesia. The research results show that teachers' cognitive flexibility abilities have a significant effect on teachers' readiness to implement the "Independent Curriculum" in schools. This can be seen from the significance score of 0.000, which is less than 0.05, so it can be concluded that teachers with high cognitive flexibility are better prepared to implement the Merdeka Curriculum in schools than teachers with low cognitive flexibility.